Experiments in Culture and Corruption : A Review - Banuri, Sheheryar; Eckel, Catherine (World Bank, Washington, DC, 2012)
Two decades of empirical evaluation have shown that corruption has a negative impact on economic growth, political stability, judicial effectiveness, democratization, educational attainment, and equality of income. However, corruption exists, persists, and varies significantly by culture. Lab studies have recently come to the forefront in identifying both the incentives and disincentives for corrupt behavior. However, lab studies on culture and corruption have led to some puzzling, contradictory results. This paper begins with a discussion of non-experimental work in this area, and evaluates the experimental findings in the context of earlier research. The authors sketch out the channels through which culture interacts with corruption (through institutions and social norms), and argue that discrepancies in experimental results may be due to differences in design (including repetition or unobserved variation in beliefs) or to differences in the response to punishment across societies. In addition to exploring design-based reasons for previous contradictory findings, avenues for future research include: behavioral responses to different types of externalities; replicating results in different countries; and utilizing the lab to formulate effective anti-corruption measures.